2020
DOI: 10.3390/ijerph17165838
|View full text |Cite
|
Sign up to set email alerts
|

Parental Perspectives and Experiences in Relation to Lifestyle-Related Practices in the First Two Years of a Child’s Life: A Qualitative Study in a Disadvantaged Neighborhood in The Netherlands

Abstract: The first two years of a child’s life are a critical period in preventing several lifestyle-related health problems. A qualitative study was conducted to explore parental experiences and perspectives in relation to lifestyle-related child-rearing practices in order to minimize risk factors at an early stage. Data were collected through interviews (n = 25) and focus groups (n = 4) with parents of children aged 0–2 years, in a disadvantaged neighborhood in Amsterdam, the Netherlands. Results showed that parents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 54 publications
(65 reference statements)
0
13
0
Order By: Relevance
“…In April 2019, weekly parent-child meetings were initiated and organized in collaboration with a ‘city farm’ located in the neighbourhood. The content and the structure of the meetings were designed in close collaboration with parents who had participated in our previous explorative study [ 21 ]. The aim of these meetings was to organize activities to promote health-related behaviours during the first 2 years of the children’s lives, through social interaction, practice and observational learning in a safe and informal setting.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In April 2019, weekly parent-child meetings were initiated and organized in collaboration with a ‘city farm’ located in the neighbourhood. The content and the structure of the meetings were designed in close collaboration with parents who had participated in our previous explorative study [ 21 ]. The aim of these meetings was to organize activities to promote health-related behaviours during the first 2 years of the children’s lives, through social interaction, practice and observational learning in a safe and informal setting.…”
Section: Methodsmentioning
confidence: 99%
“…However, several studies have shown that parents of young children are uncertain or lack knowledge about a healthy diet, daily physical activity, adequate sleep, and limited screen time for their children, and that they experience problems or are unable to facilitate a healthy environment for their child [ 21 25 ]. Moreover, the transition to parenthood is a major adjustment period and is known to be a time where the need for support is increased, since it comes with profound life changes and considerable stress [ 26 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This can happen either because of the fear of stigmatizing the child or because of the increase in the proportion of overweight children which can create a perception of excess as “normal”. [ 19 20 21 ] Another reason for this parental misconception is probably their reluctance to admit the problem, mainly because their children's diet is unhealthy. [ 22 23 ] Moreover, the daily parent and child interaction is often responsible for this misconception, as weight gain, especially if it is acute, may not be easily perceived.…”
Section: Discussionmentioning
confidence: 99%